Delayed Emergency Management of Testicular Torsion in a Rural Hospital Without Urologist: A Case Report - Satrio Budi Wicaksono; Yustina (The Indonesian Journal of General Medicine, 2026)
Background Testicular torsion is a time-sensitive urological emergency requiring prompt diagnosis and surgical intervention to prevent irreversible ischemia and testicular loss. International guidelines emphasize immediate surgical exploration in patients with high clinical suspicion rather than delaying intervention for confirmatory imaging. Delays are more common in rural hospitals due to limited resources and lack of urologists. Case Presentation A 13-year-old boy presented with sudden severe left scrotal pain. Physical examination revealed a hard, horizontally lying left testis with absent cremasteric reflex. The TWIST score was 6, indicating high risk of torsion. Color Doppler ultrasonography showed reduced perfusion. Surgical exploration was performed approximately 7 hours after admission, revealing intravaginal torsion exceeding 360° with non-viable testis. Left orchiectomy and right orchidopexy were performed. Postoperative recovery was uneventful. Discussion This case highlights the importance of early clinical diagnosis, utilization of the TWIST score, and prompt surgical management. Delayed intervention related to emergency department workload, operating room availability, and absence of on-site urologists contributed to testicular loss. Conclusion In rural hospitals without urologists, standardized triage using TWIST, early surgical referral, and consideration of manual detorsion are essential to reduce preventable orchiectomy.